Search for pair-produced dijet resonances in four-jet final states in pp collisions at $\sqrt{s}$=7 TeV - CMS collaboration (2207 authors) (2013)
A search for the pair production of a heavy, narrow resonance decaying into two jets has been performed using events collected in $\sqrt{s}$ = 7 TeV pp collisions with the CMS detector at the LHC. The data sample corresponds to an integrated luminosity of 5.0 inverse femtobarns. Events are selected with at least four jets and two dijet combinations with similar dijet mass. No resonances are found in the dijet mass spectrum. The upper limit at 95% confidence level on the product of the resonance pair production cross section, the branching fractions into dijets, and the acceptance varies from 0.22 to 0.005 pb, for resonance masses between 250 and 1200 GeV. Pair-produced colorons decaying into q q' are excluded for coloron masses between 250 and 740 GeV.